PENGARUH KUALITAS MAKANAN DAN MINUMAN TERHADAP KEPUASAN TAMU PADA RESTAURANT DI MANADO QUALITY HOTEL - Sony Wijanarko; Merry Adrah; Gerry Kadamehang (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
The Effect of Food and Beverage Quality on Guest Satisfaction at Restaurant in Manado Quality Hotel. This study aimed to measure, analyze and explain the effect of Food and Beverage quality on guest satisfaction at Manado Quality Hotel Restaurant. Data were collected using observation, interviews, questionnaires and documentation. The sample was taken using random sampling and the analytical method used was regression analysis and correlation coefficient to calculate how strong the influence between variable (X) and variable (Y). The final results of the study after calculating the determinant coefficient r2 = 0.493929 or 49.39% indicating that there is an effect of the quality of food and beverages on guest satisfaction of 49.39% and the remaining 50.61% is a variable change caused by factors which were not observed.